An Interprofessional Interpretation of Ontario’s CPSO End-of-Life Policy - Michael Sklar; Quinn Walker; Ellen Lewis; Karen Born; Courtney Sas (Canadian Journal of Bioethics)
In the acute care setting, we often ask families to make challenging decisions regarding their loved ones’ preferences and choices for end of life care when these individuals can no longer make those decisions themselves. This already stressful situation can be exacerbated by medical jargon and conflicting messaging from various well-meaning health care practitioners. Some of this ambiguity likely stems from medical providers’ lack of familiarity with end-of-life policies and their obligations as providers. Further, there can be discomfort for many families and clinicians about speaking about end of life, alongside varying cultural norms and expectations around death and dying.